Ethical Considerations in Patients with Obesity - Dian Permatasari (Indonesian Nutrition Association, 2022)
Obesity is an epidemic that is about to overwhelm the economic and health care structures of society. Obesity is a complex medical condition that has roots in genetic, environmental and social exposures that should not be attributed lack of willpower any more than other diseases. A supportive clinical setting for patients with obesity optimally includes comfortable, accessible waiting and examination areas with weight-sensitive reading materials; specialized medical equipment, specially designed tables and surgical equipment; and sensitive weighing procedures, including a private weighing area. Patients with obesity should be treated similarly to other patient populations that require additional care or have increased risks of adverse medical outcomes.